Effect of the Biofield Energy Treated Proprietary Test Formulation for Sleep Biomarkers in the Unpredictable Chronic Stress (UCS) Animal Model - Mahendra Kumar Trivedi; Alice Branton; Dahryn Trivedi; Gopal Nayak; Snehasis Jana (Journal of Behavior Therapy And Mental Health, 2020)
Sleep biomarkers in brain such as melatonin, BDNF (Brain-derived neurotrophic factor), PGD2 (Prostaglandin D2), leptin, orexin-A, and acetylcholine were evaluated in the unpredictable chronic stress (UCS) rodent model in the presence of Consciousness Energy Healing Treated (the Trivedi Effect®) novel test formulation in male Sprague Dawley (SD) rats using ELISA assay. The test formulation was consisted of minerals (Zn, Fe, Cu, Se, Ca, Mg), vitamins (C, E, B6, B12, D3), β-carotene, ginseng, and cannabidiol isolate. The test formulation constituents were divided into two parts, one part of each ingredient was distinct as the untreated test formulation, while the other portion of the test formulation and a group of animals received Biofield Energy Healing Treatment by a renowned Biofield Energy Healer, Mr. Mahendra Kumar Trivedi. The level of melatonin in groups viz. G5 (Biofield Energy Treated Test formulation) and G7 (15-days pre-treatment of Biofield Energy Treated Test formulation) was significantly increased by 17.6% (p≤0.01) and 16%, respectively as compared with the disease control group (G2). Brain-derived neurotrophic factor (BDNF) level in brain was increased by 5.2% in G7 group as compared with the G4. Prostaglandins D2 (PGD2) level was significantly (p≤0.001) increased by 12.7%, 18.1%, 23.7%, and 30.7% in the G6, G7, G8 (15 days pre-treatment of Biofield Energy Treated Test formulation to the Biofield Energy Treatment per se rats), and G9 (untreated test formulation to the Biofield Energy Treatment per se to the rats) groups, respectively as compared with the G2. The level of leptin after Biofield Energy Treatment and with the test formulation was altered. However, orexin-A level was significantly decreased by 37.1% (p≤0.05), 32.6%, 40.5% (p≤0.05), 44.4% (p≤0.05), and 28.2% in the G5, G6, G7, G8, and G9 groups respectively, as compared with the G2. Similarly, acetylcholine (Ach) level was significantly (p≤0.001) decreased by 42.5%, 49.2%, 40.1%, 47.9%, and 45% in the G5, G6, G7, G8, and G9 groups, respectively as compared with the G2. Overall, the results showed the significant slowdown the stress-related disease progression and its complications/symptoms in the preventive in the Biofield Energy Treatment group per se and/or Biofield Energy Treated Test formulation groups (viz. G6, G7, G8, and G9) comparatively with the disease group. The Trivedi Effect® showed increased level of melatonin and decreased levels of insomnia related brain biomarkers which might be helpful to induce better sleep in human.
Keywords: Biofield Energy Treatment